2013
DOI: 10.15580/gjer.2013.7.070313700
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Supervisory Practices of Zimbabwean School Heads

Abstract: Schools in developing countries including Zimbabwe face a host of problems related to the twin concepts of poor classroom instruction and low student achievement. According to (Boaduo, 2011a, Glanz, 2010), developing countries face common problems in providing sufficient education of high quality to their learners. Typically these challenges breakdown to matters of instructional supervision, teaching behaviours and general low learner performance. Given this context, it becomes necessary to construct new frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…These findings are in line with the Government of Zimbabwe ( 2001) through the Education Act that spells out the minimum qualifications for all teachers employed. The results of this study also support the views of Mapolisa and Tshabalala (2013) who indicated that the MoPSE sets, enforces, and supervises standards for private schools to ensure that education is provided in line with the public goals protecting the welfare of the citizens.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are in line with the Government of Zimbabwe ( 2001) through the Education Act that spells out the minimum qualifications for all teachers employed. The results of this study also support the views of Mapolisa and Tshabalala (2013) who indicated that the MoPSE sets, enforces, and supervises standards for private schools to ensure that education is provided in line with the public goals protecting the welfare of the citizens.…”
Section: Discussionsupporting
confidence: 78%
“…According to Sango, Chikohomero, Saruchera and Nyatanga (2017), District Schools Inspectors (DSIs) and Subject Inspectors (SIs) supervise all private schools in order to maintain quality and check if teachers comply with the educational policies. In support of this view, Boaduo (as cited in Mapolisa and Tshabalala, 2013) opines that the process of improving teacher instruction competences and the quality of instruction depends not only on teachers but also on how they are supervised. Supervision is an essential tool for maintaining quality in education, however, it is unfortunate that the instructional supervision is used as a fault-finding mechanism, which leads to teachers not receiving the necessary guidance and substantive support (Mapolisa & Tshabalala, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The educational and training policy of 2014 in Tanzania points out that, the heads of schools are vested with power to supervise the quality aspects of teaching and learning in jurisdiction organizations. However, public concern, astute observations and repeated educational studies indicate that there is an ongoing decline in supervision in schools worldwide today [3,4]. This decline is associated with a lack of proper supervision in schools; and has a bearing on the education-related challenges that are making it difficult for countries to achieve their educational goals than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…Global educational policies and programs alike have brought forth significant challenges to many education systems worldwide though educational policy in the twenty-first century is the key to global security, sustainability and survival (Musungu & Nasongo, 2008;Mapolisa & Sabalala, 2013;Ndebele, 2013). As a response, Ngussa (2014) denotes that this survival is guaranteed through adequate work, supervision as one of strategic survival approaches.…”
Section: Introductionmentioning
confidence: 99%